RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN PADA KOPERASI KARYAWAN PT GIKEN PRECISION INDONESIA - Riki, Riki (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2018)
The update technology in business processes is indispensable for the Organization, one of the updates that can be upgraded on the payroll. Cooperative Employees of PT Giken Precision Indonesia requires systems that support the payroll process is good for its employees, payroll system that exists on the Employee Cooperative PT Giken Precision Indonesia is still done manually, that is, do pencantatan employee data to manufacture slip salary, this led to the delay in information and data loss. To overcome these problems, required the existence of a new computerized system to improve work efficiency. The methodology used to design a computerized system: analyzing the running system, designing a new system, making the system, and the last test of the system have been made. The application which resulted in the creation of this program is the application of information system of payroll employees using the programming language Visual Basic 2008 and draft database using MySql Server. After going through the stages in accordance with the selected development methods in the implementation of payroll information system that is continuously and have follow-up testing system which consists of testing where this testing using black box testing methods which focus on the functional requirements for software testing and field testing with IE betha processing data as the value of the accuracy of the results of the selection.